The Phenomenon of Consumer Behavior of Shopee Paylater Users - Alzam Zakaria Ali, Miko Wihdan; Bawalaksana, Dhara Akbar; Ihsan, Khoizin Nur (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2025)
This research examines consumer behavior and the use of Shopee PayLater in online shopping in the Pintu Jenangan Village Community, Ponorogo. Shopee paylater is known as a service for users to shop online on the Shopee platform without having to pay directly. The type of research used is descriptive qualitative research method. This research focuses on consumer behavior, factors, and the impact of using PayLater services in online shopping by the Pintu Jenangan Village Community, Ponorogo, analyzed using Jean Baudrillard's consumer society theory. The results of the research show that there are two factors in the consumptive behavior of students using Shopee Paylater, namely: internal factors caused by emotional feelings, habits, social status, lack of financial awareness, impulsivity, and lifestyle while in terms of external factors caused by promotions and discounts, ease of access , attractive advertising, flexible payment features, reviews and testimonials, personalization technology, loyalty and rewards programs and exclusive offers. Thus, consumer behavior using Shopee Paylater can become a problem if users do not pay attention to their spending limits and financial capabilities. It is important to use Shopee Paylater wisely by considering financial needs and capabilities.